Sosialisasi Teknik Penangkapan Ikan dan Alternatif Pemanfaatan Telur Ikan Terbang Pada Musim Timur - Ronald Darlly Hukubun; Lina S. Berlianti; M. Fajar Alfikar; Friesland Tuapetel (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Flying fish of the Exocoetidae family are abundant in the east monsoon. This fish has important economic value because it is consumed by the public and its eggs are an export commodity. The problem encountered, Ambon Island fishermen only use the fish, the eggs do not. This is due to the unfavorable east monsoon and limited fishing vessels and skills, even though the utilization area is very close to settlements. Therefore socialization of fishing techniques is deemed necessary to improve people's welfare. The socialization was carried out in the Hukurila State PKK Room, Ambon City, Saturday, June 3, 2023, with 29 fishermen. Submission of material in the form of presentations, questions and answers, and discussions. The results of this activity are introducing fishing techniques and utilizing flying fish eggs as an alternative to fishing in the east monsoon. This socialization was welcomed by the fishermen and the government of the country, who agreed to realize this program the following year supported by village funds and youth.